Changes in human sperm motility and DNA fragmentation index after incubation at different temperatures following density gradient centrifugation and swim-up procedures. Issue 4 (29th November 2022) - Yang, Yan-Nan; Wang, Ling; Liu, Yu-Bing; Xue, Yun-Jing; Liu, Chen-Chen; Shi, Fei; Dai, Xue; Chian, Ri-Cheng
Abstract : Objective: The purpose of this study was to evaluate the sperm motility and DNA integrity at different temperatures to analyze whether the sperms are suitable on the second day for insemination of in vitro matured oocytes by intra-cytoplasmic sperm injection (ICSI) following density gradient centrifugation (DGC) and swim-up (SU) procedures. Methods: Semen samples were collected from 30 outpatients who visited the Center for Reproductive Medicine for semen analyses. Following sperm selection by DGC and SU procedures, the liquified semen samples were divided into three groups and incubated at 4, 25, and 37°C, respectively. Following incubation for 24, 48, and 72 hours, the sperm motility and sperm DNA fragmentation index (DFI) were analyzed. Results: Following the combination of DGC and SU procedures, the sperm motility (91.8% ± 8.6% vs . 50.8% ± 13.1%) and DFI (5.1% ± 7.9% vs . 13.0% ± 11.6%) were significantly improved ( P <0.01) compared to those without any treatment. The sperm motility of the 3 groups significantly declined ( P <0.05) post-incubation compared to that of the groups prior incubation. However, sperm motility significantly increased (76.9% ± 10.4%) ( P <0.05) at 25°C compared to that of the other 2 groups (53.5% ± 11.0% and 47.6% ± 10.2%). Sperm DFI significantly increased ( P <0.05) at 37°C following incubation for 24 and 72 hours in comparison to that of the other 2 groups. However, the sperm DFI did not significantly increase when the sperm samples were incubated at 4 (5.7% ± 5.9%) and 25°C (6.8% ± 5.6%) for 24 hours compared to that before incubation (5.1% ± 7.9%). Conclusions: These results indicate that the sperm quality, in terms of motility and DFI, can be efficiently improved by DGC in combination with SU. Following which, the sperm samples can be incubated at 25°C and be used on the second day for insemination of in vitro matured oocytes by ICSI.